Causality between GDP, Exports and Imports: Evidence from Indian Ocean RIM Associations Member Nations - Singh, Manbir; Dhami, Dr Jasdeep Kaur (The journal of contemporary issues in business and government, 2021)
The world economy is experiencing rapid changes with globalisation playing a predominant role. The Indian Ocean Rim Association for Regional Cooperation (IOR- ARC) is the product of several events. IORA contains 22 member nations. The Indian Ocean is one of the major link for international trade and sea transport. Indian Ocean RIM accounts for 2.7 billion population of the world, rich in cultural, languages, religions, traditions, arts ,cuisines and economic development with diversity. The main objective of this paper is to analyse Causality between GDP, Exports and Imports: Evidence from Indian Ocean RIM Associations Member Nations. This paper analyse the relationship between GDP, Export and Import of Indian Ocean RIM Association member nations since 1980 using the Uni Root Testing, Co-Integration and Granger Causality.